GASTROINTESTINAL BLEEDING, DESCRIPTION, ETIOLOGY, EPIDEMIOLOGY, CLASSIFICATION, CLINICAL PRESENTATION, TREATMENT AND PROGNOSIS - Geovanna Karolina Cazorla Andrade; María José Montaño Ortega; Edisson Fabricio Mejia Sarmiento; Janneth Paola Orellana Minchala; Claudia Gabriela Jara Maldonado; Estefanía Isabel Clavijo Rosales; Mauro Jacinto Moyano Urena; Mayra Alexandra Rodas Merchán; Daniel Guillermo Calle Rodas; Bryam Esteban Coello García (EPRA International Journal of Multidisciplinary Research (IJMR), 2024)
Introduction: Gastrointestinal bleeding can be divided into 2 broad categories: upper and lower bleeding. The anatomical landmark that divides upper and lower bleeds is the ligament of Treitz. Bleeding that begins above the ligament of Treitz usually presents as hematemesis or melena, while bleeding that begins below is frequently shown as hematochezia. Objective: to detail current information related to gastrointestinal bleeding, description, etiology, epidemiology, classification, clinical presentation, treatment and prognosis. Methodology: a total of 32 articles were analyzed in this review, including review and original articles, as well as clinical cases, of which 23 bibliographies were used because the other articles were not relevant to this study. The sources of information were PubMed, Google Scholar and Cochrane; the terms used to search for information in Spanish, Portuguese and English were: gastrointestinal bleeding, intestinal bleeding, ulcer, NSAID, gastro. Results: An H pylori eradication regimen should be started if H pylori is present in case of peptic ulcer. In upper gastrointestinal bleeding, hospital mortality rates are around 10%. This rate remains stable up to 1 month after hospitalization for gastrointestinal bleeding. Long-term follow-up of individuals with ADH shows that three years after admission, all-cause mortality rates approach 37%. Mortality rates were higher in women relative to men, which differs from lower gastrointestinal bleeding. Individuals with multiple hospitalizations for gastrointestinal bleeding have higher mortality rates. Long-term prognosis was worse in individuals with malignancies and variceal bleeding. Prognosis is usually worse with advancing age. For lower gastrointestinal bleeding, all-cause in-hospital mortality is low at about 4%. Conclusions: The care of patients with gastrointestinal bleeding requires coordinated and efficient interprofessional cooperation. Upper gastrointestinal bleeding (UGH) is more frequent compared to lower gastrointestinal bleeding (LGE). We have to recognize the importance of the clinical manifestations of each of these and the differential diagnoses of these alterations, in order to have a proper diagnosis and therefore start the correct treatment in a timely manner and improve the prognosis of the affected individual. For treatment, risk stratification is of vital importance as well as an assessment of the appropriate setting for treatment followed by resuscitation and supportive therapy while investigating the underlying cause and attempting to correct it.